PERANCANGAN ULANG DIMENSI SALURAN DRAINASE DI PERUMAHAN JIHAD INDAH PERSADA 2 KECAMATAN KOTO TANGAH PADANG - 1-7 . Agantrietly (Universitas Negeri Padang, 2013)
Residential Jihad Indah Persada 2 is residential standing water, even puddles that can reach a height of 140-160 cm. Existing drainage channels can not accommodate excess water discharge from the greatest rainfall. The value of the maximum daily rainfall average obtained is equal to 242.85 mm / day, the distribution used is the Gumbel distribution. The average number of water decline in intervals of 60 minutes = 0.05 m with an averagepower of absorbing soil is 290.5 ltr/m2/day and comparison of inflow and outflow is 242.85 mm> 116.46 mm (occur puddle because greater inflow than outflow). Value of the peak flow rate (Q) = 0.15 m3/s, the dimension of the channel in the residential Jihad Indah Persada 2 is a bottom width of 0.5 m, width 0.8 m and height of the peak 0.21 m. Key words : drainage channel, puddles, residential jihad indah persada 2